Weed control strip influences the initial growth of Eucalyptus grandis - Vaz da Silva, Joao Renato [UNESP]; da Costa Aguiar Alves, Pedro Luis [UNESP]; Bragion de Toledo, Roberto Estevao [UNESP] (Universidade Estadual de Maringá (UEM), Pro-reitoria Pesquisa Pos-graduacao, 2012)
Reforestation in Brazil is conventionally carried out with a 50-cm weed control strip, using mechanical or manual hoeing or herbicides. The aim of this study was to determine effects of varying the width of the herbicide-treated strip on the establishment of Eucalyptus grandis. Eucalyptus plants were transplanted in Araraquara and Altinopolis counties, São Paulo State, Brazil. In Araraquara, the following treatments were evaluated: 0, 25, 50, 75, 100 and 150-cm wide strips, treated with herbicide, on either side of the eucalyptus row; in Altinopolis, the width of the strip on either side of the eucalyptus row was 0, 25, 50, 75, 100, 125 or 150 cm. Were evaluated dry matter of leaves, branches and stem and leaf area at 270 days after planting (270 DAP), chlorophyll content (400 DAP), stem diameter and eucalyptus plants height (410 DAP). In Araraquara, the main weed was Panicum maximum, and in Altinopolis, it was Rhynchelytrum repens. For both areas, a minimum of 75 cm of treated strip was required to minimise weed interference with eucalyptus plants' development.
Keywords: reforestation; weed interference; weed competition